Maggot Optimization as Organic Waste Bioconversion in Sembubuk Village, Muaro Jambi Regency - Ade Adriadi; Rizky Desryan Syah; M. Khafid Rizaldi; Muhammad Fernando; Nur Umi Hasanah; Arel Del Kita Putra; Angely Ignatia Silalahi; Shinta Khana Afriya; Elisa Tri Erawati; Suci Rahmadhani; Rizky Fariz Diouf; Pandu Tulus Pambudi; Bela Apriani Br. Panjaitan; Ahmad Abdan Solikhin; Yuliniar Senjaya; M. Saiful Muarif (Journal Of Rural Community Development, 2026)
Sembubuk Village has great potential in the agricultural and livestock sectors, yet it faces challenges in sub-optimal organic waste management. This study aims to implement the MAGGOTIN innovation as an integrated solution through waste bioconversion technology using Black Soldier Fly (BSF) larvae. The methods included regional potential identification, community knowledge surveys, technical cultivation training, and the construction of "Rumah Maggot" as a controlled production facility. The results showed success in creating a self-sustaining BSF cultivation cycle and producing high-value derivatives, including high-protein feed pellets, ruminant vitamins, roasted dried maggots, and high-quality biofertilizer (frass). The program's implementation was not only effective in reducing environmental pollution but also succeeded in increasing the capacity of farmer groups to achieve feed and fertilizer independence. The conclusion of this study is that the MAGGOTIN innovation effectively transforms waste into productive products that support creative economy and sustainable agriculture in Sembubuk Village.